2016
DOI: 10.5194/nhess-16-1473-2016
|View full text |Cite
|
Sign up to set email alerts
|

Classification of karst springs for flash-flood-prone areas in western Turkey

Abstract: Abstract. Flash floods are caused by heavy rainfall that has become more frequent. They are more prominent in lowstorage karst regions, although karst terrain often acts as a natural flood control particularly when it is bare and dominated by conduits. A study using a hydrogeochemical approach and assessing data from several springs in different carbonate rock in western Turkey has made it possible to classify karst aquifers based on their response to heavy rainfall events. According to this aim, physico-chemi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Type Ⅱ seemed to discharge both the flow component through the epikarst zone and the baseflow from the lower reservoir, as defined by Tritz et al (2011) who used two reservoirs (i.e., the upper epikarst/soil zone and the lower vadose and saturated zone) to simulate the behavior of a karst system catchment and assumed a fast flow through the epikarst and slow baseflow from the lower reservoir. The deep groundwater rising at springs was also observed by other researchers including Moore et al (2009), Bicalho et al (2012), Demiroglu (2016), Gil-Márquez et al (2019, Lorette et al (2018), andZhu et al (2020). Some implied fast transfer through conduits unlike Tritz et al (2011).…”
Section: Type ⅱ Springsupporting
confidence: 67%
See 3 more Smart Citations
“…Type Ⅱ seemed to discharge both the flow component through the epikarst zone and the baseflow from the lower reservoir, as defined by Tritz et al (2011) who used two reservoirs (i.e., the upper epikarst/soil zone and the lower vadose and saturated zone) to simulate the behavior of a karst system catchment and assumed a fast flow through the epikarst and slow baseflow from the lower reservoir. The deep groundwater rising at springs was also observed by other researchers including Moore et al (2009), Bicalho et al (2012), Demiroglu (2016), Gil-Márquez et al (2019, Lorette et al (2018), andZhu et al (2020). Some implied fast transfer through conduits unlike Tritz et al (2011).…”
Section: Type ⅱ Springsupporting
confidence: 67%
“…The low storage seemed to cause the discharge quickly responding to rainfall not only during the typhoon event in 2000, but also in the small precipitation events in 1999 (Figure 2), and the rainfall accounting for 87% of the discharge at peak flow and continuing to flow out and contributing more than half of the discharge after the heavy rainfall stopped at S46 (Figure 11; Table 3). Similarly, Demiroglu (2016) reported that developed karst sinkholes allow fast percolation of heavy rainfall into an aquifer up to 80%, and explained that the very low storage combined with the high transmissivity means that most of the recharge will not be retained by the karst system, but will rapidly flow out to springs, rivers, lakes, or seas. In contrast, the delayed response to the storm and quick recovery to the baseflow condition after it stopped raining at S41 and S45 (Figure 11; Table 3) were probably due to the storage effect of the vadose zone, given that all three springs had flow characteristics through permeable conduits.…”
Section: Storage Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, karst aquifer systems have weak water holding capacity and water storage capacity. When the cumulative rainfall of a rainfall event is greater than the capacity of the karst conduits and fissures in aquifer systems (Gázquez, Calaforra, & Fernández‐Cortés, 2016), it is easy to trigger karst flash floods (Demiroglu, 2016; Martinotti et al, 2017). With the increasing risk of extreme weather events worldwide, the probability of sudden floods in karst watersheds has increased significantly (Gázquez et al, 2016); therefore, it is of great practical significance to study flood prevention countermeasures in karst basins.…”
Section: Introductionmentioning
confidence: 99%